Analysis of Student Needs on Multiple Intelligences Interactive Learning Media with Islamic Values - Nur Indah Rahmawati; Dimas Nugroho; Venda Mega Faniya (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2022)
The research problem was how the steps for analyzing the needs of interactive learning media based on multiple intelligences integrated with Islamic values ​​developed. This study describes the Needs Analysis of Interactive Learning Media based on Multiple Intelligence integrated with Islamic values. This type of research was qualitative research. This research was conducted to analyze the need to create interactive learning media, Inspiring Presentation, with HTML5. The method of collecting data in the research was by using interview techniques on six students of class VII and three teachers of Mathematics. Based on the needs analysis and the material analysis results, no interactive learning media contains nine multiple intelligences, which we know as Multiple Intelligences integrated with Islamic values. So it is necessary to develop further from the results of this study to get to the stage of obtaining good learning media as needed.